Khwam R. Al-Husseiny Isolation of the vancomycin resistant enterococci from different sources - Al-Husseiny , Khwam (University of Thi-Qar Journal of Science, 2019)
A total of sixty five isolates of enterococci were isolated; thirty six isolates from clinical samples (stool, urine, vaginal swabs, intra-abdominal and pelvic wounds and blood cultures) and twenty nine isolates from hospital environment (operating theaters, bed wards, floor, medical instruments, and sewage). The results revealed that 14 isolates (12.53%) were vancomycin-resistant enterococci including 8 isolates from clinical samples and 6 isolates from hospital environment. Moreover, 8 isolates (12.30%) showed intermediate resistance, and remaining (43) isolates are sensitive to vancomycin